CD38+CD39+ NK cells associate with HIV disease progression and negatively regulate T cell proliferation - Qian, Shi; Xiong, Chunbin; Wang, Meiting; Zhang, Zining; Fu, Yajing; Hu, Qinghai; Ding, Haibo; Han, Xiaoxu; Shang, Hong; Jiang, Yongjun (Frontiers in Immunology, 2022)
The ectonucleotidases CD38 and CD39 have a critical regulatory effect on tumors and viral infections via the adenosine axis. Natural killer (NK) cells produce cytokines, induce cytotoxic responses against viral infection, and acquire immunoregulatory properties. However, the roles of CD38 and CD39 expressed NK cells in HIV disease require elucidation. Our study showed that the proportions of CD38+CD39+ NK cells in HIV-infected individuals were positively associated with HIV viral loads and negatively associated with the CD4+ T cell count. Furthermore, CD38+CD39+ NK cells expressed additional inhibitory receptors, TIM-3 and LAG-3, and produced more TGF-β. Moreover, autologous NK cells suppressed the proliferation of CD8+ T and CD4+ T cells of HIV-infected individuals, and inhibiting CD38 and CD39 on NK cells restored CD8+ T and CD4+ T cell proliferation in vitro. In conclusion, these data support a critical role for CD38 and CD39 on NK cells in HIV infection and targeting CD38 and CD39 on NK cells may be a potential therapeutic strategy against HIV infection.